2003
DOI: 10.1109/tasc.2003.812212
|View full text |Cite
|
Sign up to set email alerts
|

MgB/sub 2/ thin films and Josephson devices

Abstract: Since the recent discovery of superconductivity in MgB 2 , various groups worldwide have been actively studying the growth of thin films based on this material. Impressive progress has been made, but various materials science challenges are still left to be solved. Guided by our own activities in this field, and reports presented in the literature, we reflect here on those challenges and possible ways for further improvement. Being important ingredients for many electronic applications, fabrication of Josephso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The linear extrapolation of the plot to Δ = 0 has been considered to infer the corresponding temperature mf . In Table 1, we presents the various parameters obtained by fitting the measured resistivity data to different AL and LD models using (1) [37] corresponding to both the mf values have been found using specific heat jump = 64 mJ/(mol K) [38] and (0) (from Table 1) and Coherence length anisotropy, ∼ 6 [39]. It is found that = 1.94 × 10 −2 and = 2.6 × 10 −2 corresponding to mf = 40.889 K and 40.901 K, respectively.…”
Section: Mean Field Temperaturementioning
confidence: 99%
“…The linear extrapolation of the plot to Δ = 0 has been considered to infer the corresponding temperature mf . In Table 1, we presents the various parameters obtained by fitting the measured resistivity data to different AL and LD models using (1) [37] corresponding to both the mf values have been found using specific heat jump = 64 mJ/(mol K) [38] and (0) (from Table 1) and Coherence length anisotropy, ∼ 6 [39]. It is found that = 1.94 × 10 −2 and = 2.6 × 10 −2 corresponding to mf = 40.889 K and 40.901 K, respectively.…”
Section: Mean Field Temperaturementioning
confidence: 99%
“…In addition, Mijatovic et al [34] presented a method in which the boron is deposited by sputtering, and the magnesium flux can be (independently) tuned by pulsed laser ablation. The low heat conductivity of boron significantly influences the splashing during PLD of boron.…”
Section: Are Epitaxial Films Possible?mentioning
confidence: 99%
“…The present focus is, to a large extent, directed towards the choice of suitable interlayer or barrier materials and how to fabricate MgB2/interlayer/MgB2 or MgB2/barrier/MgB2 trilayer devices. All-MgB2 multilayer junctions made in a ramp type (Mijatovic et al 2002, Mijatovic et al 2003 and step-edge (Kye et al 2003) configurations have been realized. Tunnel junctions using asgrown MgB2 thin films, AlN as a barrier and NbN counter-electrode have been reported (Saito et al 2002).…”
Section: Introductionmentioning
confidence: 99%